Division and administrative-territorial organization of the Slovenian territory at NUTS level 3 - Škratek, Gregor (Journal for Geography, 2013)
This article deals with the administrative-political division of the Slovenian territory from the formation of provinces to this time in the light of the previous geopolitical situation. When Slovenia joined the European Union (EU) on 1st of May 2004, the requirements for administrative and political division changed, since EU requires unification of the NUTS regions. Since this issue has not been satisfactorily regulated up until now, this article provides a new perspective on the creation of NUTS 3 regions.
Keywords: political geography; administrative division; NUTS regions; Slovenia